Evaluation of The Merdeka Curriculum in Islamic Education Based on Tyler’s Model: An Analysis of The Achievement of Students’ Cognitive, Affective, and Psychomotor Competencies - Firmansyah, Moch Fikry; Asrori, A; Puspitasari, Ika (Al'ulum Jurnal Pendidikan Islam, 2026)
This study aims to evaluate the effectiveness of the merdeka curriculum in Islamic education at Madrasah Ibtidaiyah Al-Hidayah Betoyo Kauman Gresik using Tyler’s goal-oriented evaluation model, focusing on cognitive, affective, and psychomotor learning outcomes. Employing a quantitative descriptive–evaluative design, data were collected from 74 students through structured questionnaires and assessment rubrics aligned with curriculum objectives. Descriptive statistical analysis was conducted to examine students’ competency achievement across the three domains. The findings reveal high achievement in the cognitive (M = 82.47) and psychomotor (M = 85.12) domains, while affective achievement reached a moderately high level (M = 79.65). The study concludes that the merdeka curriculum effectively supports holistic learning in Islamic primary education, although continuous reinforcement is recommended to strengthen affective development through reflective and value-based instructional strategies.